Impact of COVID-19 on the trade of goods and services in Spain. Issue 85 (3rd February 2021) - Minondo, Asier
Abstract : Purpose: This paper aims to analyze the impact of COVID-19 on the trade of goods and services in Spain. Design/methodology/approach: This paper uses monthly trade data at the product, region and firm level. Findings: The COVID-19 crisis has led to the sharpest collapse in the Spanish trade of goods and services in recent decades. The containment measures adopted to arrest the spread of the virus have caused an especially intense fall of trade in services. The large share of transport equipment, capital goods, products that are consumed outdoors (i.e., outdoor goods) and tourism in Spanish exports has made the COVID-19 trade crisis more intense in Spain than in the rest of the European Union. Practical implications: The nature of the collapse suggests that trade in goods can recover swiftly when the health crisis ends. However, COVID-19 may have a long-term negative impact on the trade of services that rely on the movement of people. Originality/value: It contributes to understand how COVID-19 has affected the trade in goods and services in Spain.